2020
DOI: 10.1093/gigascience/giaa136
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a differentiation stall in epithelial mesenchymal transition in histone H3–mutant diffuse midline glioma

Abstract: Background Diffuse midline gliomas with histone H3 K27M (H3K27M) mutations occur in early childhood and are marked by an invasive phenotype and global decrease in H3K27me3, an epigenetic mark that regulates differentiation and development. H3K27M mutation timing and effect on early embryonic brain development are not fully characterized. Results We analyzed multiple publicly available RNA sequencing datasets to identify diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Differential expression of EMT-related genes has been shown to be a feature of H3.3K27M DMG. Genes typically expressed post-EMT are downregulated in H3.3K27M tumors (Sanders et al 2020). We clustered iDMG on a list of EMT-related genes (Sanders et al 2020) and showed that H3.3 status highly influences their expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential expression of EMT-related genes has been shown to be a feature of H3.3K27M DMG. Genes typically expressed post-EMT are downregulated in H3.3K27M tumors (Sanders et al 2020). We clustered iDMG on a list of EMT-related genes (Sanders et al 2020) and showed that H3.3 status highly influences their expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…THP relative to TP iDMG show decreased expression of TWIST1 and FN1 , genes that are expressed post-EMT in normal tissue and downregulated in H3.3K27M tumors (Fig. 3F) (Sanders et al 2020). This finding contrasts with increased TWIST1 and FN1 expression in adult GBM compared to normal tissue, highlighting the unique biology of H3.3K27M DMG (Brennan et al 2013; Elias et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Looking at published data of human tumors where investigators compared H3.3K27M mutant human high-grade glioma to H3.3WT high-grade gliomas, we note some differences and some similarities between our observations in our genetic models and the reported effects of H3.3K27M in patient data. For example, a recent comparison of human H3.3K27M pediatric highgrade glioma to non-K27M pediatric high-grade gliomas identified the following top 5 Hallmark GSEA pathways to be significantly enriched in K27M tumors: myogenesis, UV response down, Kras signaling down, EMT, and estrogen response late (Sanders et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Looking at published data of human tumors where investigators compared H3.3K27M mutant human high‐grade glioma to H3.3WT high‐grade gliomas, we note some differences and some similarities between our observations in our genetic models and the reported effects of H3.3K27M in patient data. For example, a recent comparison of human H3.3K27M pediatric high‐grade glioma to non‐K27M pediatric high‐grade gliomas identified the following top 5 Hallmark GSEA pathways to be significantly enriched in K27M tumors: myogenesis, UV response down, Kras signaling down, EMT, and estrogen response late (Sanders et al, 2020). Interestingly, three of these were significantly enriched in our analysis comparing H3.3K27M to H3.3WT tumors initiated in Olig2‐expressing progenitors: (1) myogenesis (2) Kras signaling down, and (3) EMT while only one of these, UV response down was significantly enriched in our analysis comparing H3.3K27M to H3.3WT tumors initiated in Nestin expressing progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of H3 K27M mutation in children and the effect on embryonic, neonatal, and childhood brain development have not been characterized. 42 In addition, the relationship between spinal cord DMG and supratentorial DMG regarding genetic alterations is also not clear, but spinal cord high-grade glioma in children and adults frequently harbors H3 K27M mutations. 66 In a 2018 study by Castel et al, investigating the epigenetic profile of H3 K27M-mutant tumors in a group of 215 children with pediatric high grade gliomas, it was found that subtypes of H3 K27M-mutant tumors were more accurately differentiated based on their methylation profile and gene expression, rather than their location, particularly when comparing supra-and infratentorial tumors.…”
Section: Genetic Characteristics and Cell Of Originmentioning
confidence: 99%